Photoresponsive N, N′-disubstituted indigo derivatives. (May 2020) - Nobre, Danîela C.; Cunha, Carla; Porciello, Alessandro; Valentini, Federica; Marrocchi, Assunta; Vaccaro, Luigi; Galvão, Adelino M.; de Melo, J. Sérgio Seixas
Abstract: The synthesis and a comprehensive characterization of the excited state properties of five N, N′-substituted indigo (Ind ) derivatives (acetyl-, benzoyl-, methoxybenzoyl-, nitrobenzoyl- and chlorobenzoyl-) was undertaken in various solvents and temperatures. In the excited state, rotation around the central double bond was found with N, N′-diacetylindigo (DAI ) and N, N′-dibenzoilindigo (DBI ) derivatives. Both DAI and DBI acyl derivatives show rotation in the excited state around the central C–C bond, leading to a conical intersection (CI). Steric hindrance prevents DBI from accomplishing full rotation (which consequently does not fully isomerize) with two conformers being experimentally found from both fs-transient absorption and time-resolved emission measurements. For DAI, the fluorescence decays are single exponential (varying from 2790 ps in 2MeTHF to 7520 ps in MCH), while fs-TA indicates the presence of two species, with lifetimes, in 2MeTHF, of 33 ps and 2790 ps. All the acyl derivatives show blue shifted absorption and emission from the parent indigo dye due to stabilization of the π HOMO orbital in the S1 π*←π transition by delocalization to the acyl carbonyl. The extent of blue shift among the different acyl derivatives is found to depend on the geometric constraints imposed on the dihedral angle between indigo and the acyl group. With the DBI derivatives, interconversion between the two conformers in the excited state leads to rate constant values ranging from 1.3 × 10 10 s −1 (in MeTHF) to 3.6 × 10 9 s −1 for the nitrobenzoyl-DBI derivative (in dioxane). Highlights: N, N′-diacetylindigo (DAI ) and N, N′-dibenzoilindigo (DBI ) derivatives show different excited state behavior. In contrast with indigo, DAI and DBI show photoisomerization. Steric hindrance leads to the formation of two conformers in DBI . DAI and DBI derivatives are found strongly sensitive to the solvent's polarity.